An innovative ternary composite paper of graphene and Fe3O4 decorated multi-walled carbon nanotube for ultra-efficient electromagnetic interference shielding and fire-resistant properties. (June 2022) - Zhou, Juanjuan; Tao, Hongji; Xia, Li; Zhao, Huidong; Wang, Yong; Zhan, Yuanyuan; Yuan, Bihe
Abstract: Herein, Fe3 O4 modified multi-walled carbon nanotube (Fe3 O4 @MWCNTs) heterostructure has been synthesized by a one-pot simplified coprecipitation method. After introducing it into graphene oxide dispersions, Fe3 O4 @MWCNTs/reduced graphene oxide (RGO) composite paper was prepared by evaporation-assisted self-assembly and hydrazine hydrate vapor reduction. The composite paper's electrical conductivity, electromagnetic interference (EMI) shielding and fire-resistant properties were investigated by four-point probe method, network analysis and combustion test method, respectively. The EMI shielding effectiveness (SE) can be adjusted by the filling amount of Fe3 O4 @MWCNTs and paper's thickness. When the thickness of the composite paper is approximately 0.6 mm and the mass fraction of Fe3 O4 @MWCNTs is 2%, the total SE of the composite paper in the X-band reaches 45.9 dB, which is 31.14% higher than that of the pure RGO paper (∼35 dB). Therefore, the Fe3 O4 @MWCNTs/RGO composite paper prepared in this study is a promising lightweight shielding material, especially suitable for various harsh natural high temperature environments. Graphical abstract: Image 1 Highlights: Fe3 O4 @MWCNTs were synthesized by a one-pot simplified precipitation method. The electromagnetic shielding effectiveness of Fe3 O4 @MWCNTs/RGO paper was explored. Fe3 O4 @MWCNTs/RGO composite paper possesses unprecedented fire resistance performance.